The anticentre old open cluster NGC 1883: radial velocity and metallicity - Villanova, S. (2007)
Having already reported on the first photometric study of the intermediate-age open cluster NGC 1883, in this paper we present the first spectroscopic multi-epoch investigation of a sample of evolved stars in the same cluster. The aim is to derive the cluster membership, velocity and metallicity, and to discuss recent claims in the literature that NGC 1883 is as metal-poor as globular clusters in the halo. Besides, as it is one of the few outer Galactic disc intermediate-age open clusters known so far, it is an ideal target to improve our knowledge of the Galactic disc radial abundance gradient, which is a basic ingredient for any chemical evolution model of the Milky Way. The new data we have obtained allow us to make the basic parameters of NGC 1883 more reliable. We find that the cluster has a mean metallicity of [Fe/H] = −0.20 ± 0.22, from which we infer an age (650+70 −70 Myr) close to that of Hyades and a Galactocentric distance of 12.3+0.4 −0.2 kpc. The metal abundance, kinematics and position make NGC 1883 a genuine outer disc intermediate-age open cluster. We confirm that in the outer Galactic disc the abundance gradient is shallower than in the solar vicinity.